Respostas
respondido por:
0
(√1/2)^2t-4 = (2³)^-t +2 ---------> [(1/2)^1/2]^2t - 4 = [(1/2)^-3]^-t + 2
(1/2)^t - 2 = (1/2)^3t - 6 -------> bases iguais expoentes iguais. então
t - 2 = 3t - 6 -------> t - 3t = -6 + 2 ------> - 2t = - 4 (-1) 2t = 4 -----> t = 4/2
t = 2 S = { 2 }
(1/2)^t - 2 = (1/2)^3t - 6 -------> bases iguais expoentes iguais. então
t - 2 = 3t - 6 -------> t - 3t = -6 + 2 ------> - 2t = - 4 (-1) 2t = 4 -----> t = 4/2
t = 2 S = { 2 }
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás